2020
DOI: 10.1002/mgg3.1114
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequencing in cytogenetics: Comparison of short‐read and linked‐read approaches for germline structural variant detection and characterization

Abstract: Background Structural variants (SVs) include copy number variants (CNVs) and apparently balanced chromosomal rearrangements (ABCRs). Genome sequencing (GS) enables SV detection at base‐pair resolution, but the use of short‐read sequencing is limited by repetitive sequences, and long‐read approaches are not yet validated for diagnosis. Recently, 10X Genomics proposed Chromium, a technology providing linked‐reads to reconstruct long DNA fragments and which could represent a good alternative. No study has compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 43 publications
2
10
1
Order By: Relevance
“…Notably, beside short read standard WGS we also performed linked‐read sequencing (10x genomics) to see whether this technology could overcome any of the technical challenges encountered through WGS and analysis (Supplementary Figure 8). Consistent with other reports, we did not find any significant advantage and it is now discontinued 22 . Interestingly sequencing of the insertion point revealed the exact same sequence for all patients and the genotyping of some individuals revealed a common shared haplotype.…”
Section: Discussionsupporting
confidence: 91%
“…Notably, beside short read standard WGS we also performed linked‐read sequencing (10x genomics) to see whether this technology could overcome any of the technical challenges encountered through WGS and analysis (Supplementary Figure 8). Consistent with other reports, we did not find any significant advantage and it is now discontinued 22 . Interestingly sequencing of the insertion point revealed the exact same sequence for all patients and the genotyping of some individuals revealed a common shared haplotype.…”
Section: Discussionsupporting
confidence: 91%
“…It uses microfluidics partitions to produce droplet particles and avoids any fragmentation, making it ideal for sequencing high molecular weight DNA of 50 kbs or higher. More importantly, the linked-read method allows mapping the reads from the repetitive regions where SV breakpoints are often located [ 32 , 33 ]. Recent studies have demonstrated the utility of the linked-read method for detecting complex SVs in a variety of samples [ 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study reported that linked-read sequencing produced scalable and comprehensive information on SVs as compared to short-read sequencing. Later, Uguen et al compared the linked-read method with short read-based WGS to detect SVs [ 33 ]. The study reported that linked-read sequencing could not improve the detection or characterization of SVs.…”
Section: Introductionmentioning
confidence: 99%
“…While linked-reads (e.g. 10x Genomics) seem promising, especially for cases in repetitive elements, the technique and detection tools need further development [17].…”
Section: Introductionmentioning
confidence: 99%